Corrections on Grammar, Sentence Variety and Developing Detail to Qualify Academic Essay of Indonesian Learners - Solikhah, Imroatus (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
This experimental research examines: (1) significant differences of corrections on grammar, sentence variety and developing details on the quality of the essay by Indonesian learners; and (2) different effect of corrections on grammar, sentence variety, and developing details on the quality of the essay. Treatments for each were served as follows: corrections on grammar for the group A (22), corrections on sentence variety for the group B (20), and corrections on the developing details for the group C (24). Data were analyzed using One-Way Anova Test. The study revealed: (1) As the teaching technique, corrections on grammar, sentence variety and developing details were significantly different; (2) Contribution on the differences respectively came from sentence variety (t=4.377), developing details (t=3.933), and grammar (t=3.756). Upon beta test, contribution varied from sentence variety (58.5%), developing details (46.5%), and grammar (38.6%). Evidently, sentence variety is the most dominant technique to improve quality of the essay up to 58.5%.